2010
DOI: 10.1371/journal.pone.0014107
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Induce a Phenotype Shift in Differentiated Endothelial Cells towards PDGF/PDGFRβ Axis-Mediated Angiogenesis

Abstract: BackgroundEndothelial Progenitor Cells (EPC) support neovascularization and regeneration of injured endothelium both by providing a proliferative cell pool capable of differentiation into mature vascular endothelial cells and by secretion of angiogenic growth factors.ObjectiveThe aim of this study was to investigate the role of PDGF-BB and PDGFRβ in EPC-mediated angiogenesis of differentiated endothelial cells.Methods and ResultsConditioned medium from human EPC (EPC-CM) cultured in hypoxic conditions containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…These findings were in accordance with the hypothesis that stem cells with long-term engraftment capabilities were predominantly located at the lowest end of an oxygen gradient in the bone marrow, in hypoxic regions containing sinusoids rather than capillary structures [21]. Other studies have shown that stem cells were resistant to hypoxia-induced apoptosis [14], and hypoxia induced the production and secretion of factors that stimulate inflammation and neovascularization [22,23]. The present study confirmed the hypoxia-resistance of MSCs and showed the partial preservation of their innate properties in hypoxic versus normoxic cells.…”
Section: Discussionsupporting
confidence: 90%
“…These findings were in accordance with the hypothesis that stem cells with long-term engraftment capabilities were predominantly located at the lowest end of an oxygen gradient in the bone marrow, in hypoxic regions containing sinusoids rather than capillary structures [21]. Other studies have shown that stem cells were resistant to hypoxia-induced apoptosis [14], and hypoxia induced the production and secretion of factors that stimulate inflammation and neovascularization [22,23]. The present study confirmed the hypoxia-resistance of MSCs and showed the partial preservation of their innate properties in hypoxic versus normoxic cells.…”
Section: Discussionsupporting
confidence: 90%
“…PDGFRβ expression has also been noted in the angiogenic ECs in glioblastoma multiforme (39). Furthermore, blocking PDGFRβ in HUVECs blunted the angiogenic response induced by endothelial progenitor cell-conditioned media (40). Thus, misexpression of PDGFRβ in HemECs may contribute to the increased proliferation in HemECs and abnormal angiogenesis in IH.…”
Section: Discussionmentioning
confidence: 94%
“…In additional, integrin ␣ V ␤ 5 promotes angiogenesis via a pathway that is distinct from integrin ␣ V ␤ 3 -dependent angiogenesis. Integrin ␣ V ␤ 5 is also essential for the differentiation of endothelial progenitors to differentiated endothelial cells (34,35). Therefore, further investigation of integrin ␣ V ␤ 5 -tropoelastin interactions could lead us to a better understanding of these disease and physiological states.…”
Section: Discussionmentioning
confidence: 99%